Kulliyāt-i Valī - Valī,Hāšimī, Nūr-al-Ḥasan (Qaumī Kaunsil barāʾe Faroġ-i Urdū Zabān, Vizārat-i Taraqqī-i Insānī Visāʾil, Ḥukūmat-i Hind, 2008)
A collection of poetry of an Urdu poet with an introduction and an assessment of the language of poet by Dr. Abdussattar Siddiqui
Poems. - Includes index. - Includes bibliographical references. - In arab. Schrift, Urdu. - Reprint. Originally published, Lakhnaʿu : Uttar Pradesh Urdū Akādmī, 1989. - Title on t.p. verso in roman: Kulliyat-e-Wali
Keywords: Urdu poetry